Production and characterization of polyetherimide mats by an electrospinning process - Sato, Daniela Mitsuko [UNESP]; Guerrini, Lilia Müller; De Oliveira, Mauricio Pinheiro; Hein, Luis Rogério De Oliveira [UNESP]; Botelho, Edson Cocchieri [UNESP] (IOP Publishing, 2018)
Polyetherimide (PEI) is an amorphous, thermoplastic polymer with high heat resistance and high strength. The production of PEI fibers using electrospinning process is very attractive because this process can produce fibers with nanometric diameters, high strength and good flexibility. Polymeric solutions of PEI with 1-methyl-2-pyrrolidone (NMP) were prepared at fixed proportions (18/82, 20/80 and 22/78% w/v) and were used to produce mats using an electrospinning process. The effect of solution concentration, applied voltage and tip-to-collector distance on the properties of the PEI mats were examined. The goal of this work was to understand the effect of the various electrospinnig parameters on the properties of the PEI mats. The thermal degradation behavior, chemical structure and morphology of the PEI mats were characterized by thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM), respectively. Fibers with diameters around 150 nm were produced by the electrospinning and the most appropriate processing conditions were: 20/80% w/v of PEI/NMP, collector distance of 5 cm and voltage of 25 kV.
Keywords: electrospinning; nanofibers; non-woven mats; polyetherimide; polymer solution